2019
DOI: 10.1016/j.arthro.2019.05.035
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Stump Sparing or Footprint Exposing? Management of the Tibial Remnant During Posterior Cruciate Ligament Reconstruction

Abstract: Surgical management of an isolated grade III posterior cruciate ligament tear has been enveloped in debate since the first reconstruction technique report was written by Hey Groves in 1919. With the evolution of arthroscopy, party lines have been drawn over tibial inlay versus transtibial techniques, as well as single-versus double-bundle techniques. More subtle controversy exists regarding autograft versus allograft, outside-in versus inside-out drilling, and treatment of the tibial footprint of the posterior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…6,7 The distinct attachment sites of the 2 PCL bundles not only are suggestive of their synergistic and co-dominant role in knee biomechanics but also offer a technical advantage for safe tunnel placement when double-bundle reconstruction is attempted. The study by Forsythe et al 5 adds to the series of recent work that has attempted to recognize important aspects in PCL reconstruction, such as the position of the femoral tunnel, 8 the importance of fixation, 9 the timing from injury to reconstruction, 10 the graft bending angle, [11][12][13] the role of the tibial slope, 14 the role of remnant tissue, 15,16 and the optimization of grafts. 17,18 The number of published articles about PCL injury showed an exponential increase in the past decade, reaching 76.9 and 82.9 articles published per year in the PubMed and Scopus databases, respectively (Fig 1).…”
Section: See Related Article On Page 2875mentioning
confidence: 99%
“…6,7 The distinct attachment sites of the 2 PCL bundles not only are suggestive of their synergistic and co-dominant role in knee biomechanics but also offer a technical advantage for safe tunnel placement when double-bundle reconstruction is attempted. The study by Forsythe et al 5 adds to the series of recent work that has attempted to recognize important aspects in PCL reconstruction, such as the position of the femoral tunnel, 8 the importance of fixation, 9 the timing from injury to reconstruction, 10 the graft bending angle, [11][12][13] the role of the tibial slope, 14 the role of remnant tissue, 15,16 and the optimization of grafts. 17,18 The number of published articles about PCL injury showed an exponential increase in the past decade, reaching 76.9 and 82.9 articles published per year in the PubMed and Scopus databases, respectively (Fig 1).…”
Section: See Related Article On Page 2875mentioning
confidence: 99%
“…Recent studies have shown that preserving the PCL stump and posterior septum during PCLR is essential for graft survival because these structures are rich in mechanoreceptors and blood vessels [ 14 16 ]. Konrads et al followed up 21 patients with intraoperative preservation of the posterior septum from 6 to 12 months, all patients had no joint effusion, and the mean difference in tibial posterior displacement on stress radiographs was 4.1 mm on the healthy and affected side [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the PCL remnant is helpful for revascularization of grafts, thereby promoting graft healing. 10 The mechanoreceptors in remnant fibers also preserve proprioception. 5,14,15 Moreover, several authors have demonstrated that the PCL remnant works like a soft tissue cushion to prevent the “killer-turn” effect at the tunnel orifice.…”
mentioning
confidence: 99%